Key factors which concur to the correct therapeutic evaluation of herbal products in free radical-induced diseases - Mancuso, Cesare (Frontiers in Pharmacology, 2015)
For many years now the world's scientific literature has been perfused with articles on the therapeutic potential of natural products, the vast majority of which have herbal origins, as in the case of free radical-induced diseases. What is often overlooked is the effort of researchers who take into consideration the preclinical and clinical evaluation of these herbal products, in order to demonstrate the therapeutic efficacy and safety. The first critical issue to be addressed in the early stages of the preclinical studies is related to pharmacokinetics, which is sometimes not very favorable, of some of these products, which limits the bioavailability after oral intake. In this regard, it is worthy underlining how it is often unethical to propose the therapeutic efficacy of a compound on the basis of preclinical results obtained with far higher concentrations to those which, hopefully, could be achieved in organs and tissues of subjects taking these products by mouth. The most widely used approach to overcome the problem related to the low bioavailability involves the complexation of the active ingredients of herbal products with non-toxic carriers that facilitate the absorption and distribution. Even the induction or inhibition of drug metabolizing enzymes by herbal products, and the consequent variations of plasma concentrations of co-administered drugs, are phenomena to be carefully evaluated as they can give rise to side-effects. This risk is even greater when considering that people lack the perception of the risk arising from an over use of herbal products that, by their very nature, are considered risk-free.